Does austerity drive public service innovation? Evidence from shared senior management teams in local government. Issue 2 (23rd February 2018) - Bello, Benedetta; Downe, James; Andrews, Rhys; Martin, Steve
Abstract : Shared senior management teams are a recent and radical response to financial austerity. They aim to improve the efficiency of public services without the disruption, controversy and transaction costs associated with full-blown organizational mergers. This paper assesses the adoption of this management innovation by English district councils, identifies enablers and barriers to its effective implementation, offers a preliminary assessment of its impacts, and draws out practical lessons for policy-makers.